Effects of Body Posture and Different Exercise Intensity on Athletes' Limb Injury. (28th June 2022) - Jin, Di; Ma, Qian
Abstract : The purpose of this study was to solve the problem of the influence of body posture and different exercise intensity on athletes' limb injuries, to meet the needs of understanding athletes' injuries, and to make up for the lack of investigations on athletes' limb injuries; this also increases the chances of an athlete avoiding injury. Severe acute sports injuries of high-level gymnasts endanger the personal safety of athletes. Many movements in gymnastics are done in the air much higher than the ground, and there is no fulcrum when the athlete does the movements; this just can only maintain balance and change your body posture through your own feelings, a slight error can easily cause your head or upper body to fall down, and the fragile spine cannot withstand the strong impact of the ground, resulting in high vertebral fractures, high paraplegia, and even death. Therefore, through a survey of 126 rhythmic gymnasts who participated in the 2011 "China Art Sports Cup" China Rhythmic Gymnastics Championship, a total of 172 injuries were found in 136 gymnasts, and the injury risk analysis was carried out from the main characteristics of the injuries.